The determinants of earnings management in Nigeria - Mustapha, Khadija; Svitlík, Jan, 1987-; Procházka, David, 1979 říjen 10.-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2022)
From 2012 through 2020, this research examines the factors that influence earnings management in a sample of Nigerian businesses. Data from 60 companies listed on the Nigerian stock exchange were used to conduct an empirical investigation. The modified Jones model 1995 was used to estimate the dependent variable (discretionary accruals as a proxy for earnings management). This model's residuals (discretionary accruals) were regressed on a set of independent characteristics that were thought to affect earnings management. Four out of the five variables studied had a substantial impact on earnings management (board size, board independence, firm size, and performance). Dividend policy, on the other hand, was not significant for Nigerian firms as majority of the listed firms are not paying dividend thus it is eliminated as a potential incentive for earnings management. Overall, the findings of the paper show that factors do influence earnings management in Nigerian firms, making it necessary for Nigerian regulatory authorities to establish effective corporate governance laws that will strengthen and promote corporate governance credibility. In terms of transparency and accountability, Nigeria has the most significant problem. As a result, the study suggests that robust corporate governance policies can reduce the discretionary flexibility of businesses and managers to manipulate earnings by minimizing information asymmetry or non-transparency and boosting company creditability
Vedoucí práce: Jan Svitlík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses